1993
DOI: 10.1007/bf02600112
|View full text |Cite
|
Sign up to set email alerts
|

Internal medicine housestaff and attending physician perceptions of the impact of the New York State section 405 regulations on working conditions and supervision of residents in two training programs

Abstract: Housestaff had more positive attitudes about the impact of the mandated changes in working conditions for residents than did attending physicians in the same institutions. The major benefits seen by residents were less fatigue and more spare time. There was no consensus about whether these changes had a positive impact on internal medicine practice and clinical supervision. There was some concern that a shift-work mentality is developing among residents and that continuity of patient care has suffered. Thus, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Under the New York State Health Code (revised Section 405), which has been copied widely (Kelly et al, 1991), residents in emergency departments now are limited to 12-hour shifts. Those in other hospital departments may not average more than 80 hours per week over a four-week period and they may not work more than 24 hours consecutively, with at least a 24-hour period of non-working time each week (Conigliaro et al, 1993).…”
Section: Notesmentioning
confidence: 99%
“…Under the New York State Health Code (revised Section 405), which has been copied widely (Kelly et al, 1991), residents in emergency departments now are limited to 12-hour shifts. Those in other hospital departments may not average more than 80 hours per week over a four-week period and they may not work more than 24 hours consecutively, with at least a 24-hour period of non-working time each week (Conigliaro et al, 1993).…”
Section: Notesmentioning
confidence: 99%
“…New working regulations have been introduced in an attempt to deal with what is considered, by many, to be harsh and unacceptable working conditions. The debate over and outcome of these interventions continues [8-10]. …”
Section: Introductionmentioning
confidence: 99%
“…4 Studies in New York, which has a 14-year history of having state-regulated duty hour limits for residents, have shown that duty hour limits reduced resident fatigue and allowed more time for reading and for personal pursuits with little change in in-service exam scores and quality of patient care. 5,6 More recently, two studies have demonstrated that limiting intern work shifts during an Intensive Care Unit rotation decreased medical errors. 7,8 Those involved in graduate medical education, however, have long struggled with competing priorities that surround the issue of resident service versus education.…”
mentioning
confidence: 99%